Land Abandonment in the Mediterranean Effects on Butterfly Communities with Respect to Life History Traits - Šlancarová, Jana (Jihočeská univerzita, 2016)
This thesis deals with the effects of changing land use, following landscape abandonment, on butterfly communities in the Mediterranean Basin. It consists of three case studies. The first focuses on the effects of forest encroachment on butterflies in the Southern Balkans; the second studies butterfly communities in Portuguese 'montados' and the third explores demography and life histories of three co-occurring Papilionidae butterfly species (Archon apollinus, Zerynthia polyxena and Zerynthia cerisy) in Greek Thrace. The results describe shifts in butterfly communities, detectable even at the level of individual species life history traits, with increasing forest encroachment. The preference of range-restricted Mediterranean endemics for either grasslands or open woodland formations contributes to falsifying the forested Mediterranean hypothesis, favouring a hypothesis of finely grained landscape mosaic instead. This mosaic is currently threatened by land use change and biodiversity homogenisation. Maintaining habitat and landscape heterogeneity is crucial for conserving the Mediterranean biodiversity hot-spot.
Land Abandonment in the Mediterranean Effects on Butterfly Communities with Respect to Life History Traits
Keywords: Lepidoptera; life-history; succession; land-use changes; functional trait; Mediterranean; oviposition; phenology; oceanitycontinentality gradient; climate Quercus suber; Lepidoptera; life-history; succession; land-use changes; functional trait; Mediterranean; oviposition; phenology; oceanitycontinentality gradient; climate Quercus suber